Preferences and Decisions Models and Applications - Greco, Salvatore; Marques Pereira, Ricardo Alberto; Squillante, Massimo; Yager, Ronald R.; Kacprzyk, Janusz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume draws mostly on papers presented at the TRENTO 2009 international workshop on Preferences and Decisions, jointly organized by the University of Trento and the University of Sannio at Benevento (Italy). Since its first edition in 1997, the renowned international workshop series TRENTO aims at providing an informal but effective opportunity for sharing and discussing the recent research developments in the field of preference modeling and decision theory, bringing together some of the world$1 (Bs leading experts in this active interdisciplinary area of research. In particular, the scope of the international workshop TRENTO 2009 covered a wide range of topics, such as preference representation and rationality, machine intelligence and automation in decision making, uncertainty modeling, probabilistic and possibilistic decision models, cooperative game theory and coalition formation, aggregation functions and multicriteria decision making, fuzzy set theory and fuzzy logic for decision making, algebraic structures, quantum dynamics, complex network models and negotiation, interactive dynamics and consensus reaching in multiagent decisions, optimization and operational research for decision making. The contributes have been proposed by authors that are among the most recognized scientists in the respective research domains. This volume also provides an opportunity, to colleagues and friends of Mario Fedrizzi, Benedetto Matarazzo, and Aldo Ventre, for celebrating and thanking them for their continuing and stimulating scientific work.s
Continuous Utility Functions for Nontotal Preorders: A Review of Recent Results -- Risk Assessment of SLAs in Grid Computing with Predictive Probabilistic and Possibilistic Models -- From Benchmarks to Generalised Expectations -- Memory Property in Heterogeneously Populated Markets -- From Comparative Degrees of Belief to Conditional Measures -- Delay and Interval Effects with Subadditive Discounting Functions -- Pairwise Comparison Matrices: Some Issue on Consistency and a New Consistency Index -- On a Decision Model for a Life Insurance Company Rating -- Qualitative Bipolar Decision Rules: Toward More Expressive Settings -- The Dynamics of Consensus in Group Decision Making: Investigating the Pairwise Interactions between Fuzzy Preferences -- Fuzzy Preference Relations Based on Differences -- Indices of Collusion among Judges and an Anti-collusion Average -- Scoring Rules and Consensus -- Dominance-Based Rough Set Approach to Interactive Evolutionary Multiobjective Optimization -- Supporting Consensus Reaching Processes under Fuzzy Preferences and a Fuzzy Majority via Linguistic Summaries -- Decision Making in Social Actions -- Coherence for Fuzzy Measures and Applications to Decision Making -- Measures for Firms Value in Random Scenarios -- Thin Rationality and Representation of Preferences with Implications to Spatial Voting Models -- Quantum Dynamics of Non Commutative Algebras: The SU(2) Case -- Benefits of Full-Reinforcement Operators for Spacecraft Target Landing -- Neural Networks for Non-independent Lotteries -- Weak Implication and Fuzzy Inclusion -- The TOPSIS Method and Its Application to Linguistic Variables -- Information Fusion with the Power Average Operator.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).